World Bank Research Digest, Vol. 2(3) - World Bank (Washington, DC, 2014)
In this issue: poverty mapping: testing the methodology in Minas Gerais; focus: international migration and development; schooling in developing countries, standards, harmonization, and trade: new empirical evidence; improving nutrition through community growth promotion in Uganda; measuring micro enterprise profits: what is the best method? And public spending and outcomes: does governance matter?